Cultural Organization and Quality of Nursing Work Life on Nurses Performance and Job Satisfaction in Dr. Soetomo Hospital, Surabaya - Winasih, Rini; Nursalam, Nursalam; Kurniawati, Ninuk Dian (Universitas Airlangga, 2015)
Introduction: Efforts to improve the quality of hospital services should be along with the efforts to improve the quality of nursing services. Quality of service is influenced by the organizational culture. The main objective of this study was to explain the effect of organizational culture and quality of nurses work life (QNWL) on nurses performance and job satisfaction in Dr. Soetomo Hospital, Surabaya. Methods: This study used explanatory survey research design with cross sectional approach. The study population was all Civil Servants nurses working at Surgical Wards, Dr. Soetomo Hospital. The study sample comprised 95 nurses selected with cluster sampling. Data were analyzed using partial least square. Results: The results showed that there was influence of objective factors on organizational culture. Individual factors had no influence on QNWL. Social and environmental factors affected QNWL. Operational factors influenced QNWL. Administrative factors affected QNWL. Organizational culture influenced QNWL. QNWL affected nurses performance. QNWL significantly affected nurses job satisfaction. Nurses job satisfaction affected nurses performance. Discussion: Strong organizational culture, which can create good quality of work life for nurses, can improve the performance and job satisfaction of nurses in Dr. Soetomo Hospital. Further studies needs to be done to analyze the effect of empowerment and job involvement on the quality of nurses work life.Keywords:Â Â cultural organization, quality of nursing work life, performance and job satisfaction, nurse